Qualitative research in journalism - A.S. de Beer (Communicare)
Among communication researchers as well as journalists a growing scepticism and even disillusionment with regard to the validity, applicability and contribution of quantitative research models are becoming increasingly noticable. Partly in response to this discontent renewed attention is focused on the qualitative approach. This approach, it is argued, is especially applicable to researching the more fundamental problems of journalism. A major point of departure of the qualitative approach according to Clifford Christians, who is one of the more productive proponents of this approach, is in defining communication as a unique human act. Attributes of this approach include the following: emphasis on participant observation as technique for data collection, the contextualisation of communicative behaviour, maximalisation of comparisons of natural and socially identifiable groups and situations, refutation of the idea of neutral objectivity, and finally, the importance of intersubjective reliability. It is concluded that the qualitative approach should form an integral part or compontent of any encompassing research strategy.